IMPLEMENTATION OF GOLD CARD PROJECT AS AN EMPLOYEE RECOGNITION PROGRAM AT SOFITEL BALI NUSA DUA BEACH RESORT - I Putu Wika Saputra; I Ketut Astawa; I Nyoman Rajin Aryana (Journal of Applied Sciences in Travel and Hospitality, 2018)
Engaging the employee is one of the challenges currently faced by the companies. Without good human resource management, the company will not be able to run effectively. The purpose of this study is to find out in-depth the latest employee recognition program implemented at Sofitel Bali Nusa Dua Beach Resort which is called “Gold Card” project. An in-depth interview was performed to get the details of the program. To enhance the result, a simple survey questionnaire was given to 60 employees to gather some feedback about the implementation of the project. The result of the research indicated that the “Gold Card” project is well received and is supported by the employee.